Price Determination Model of World Vegetable and Petroleum - Alam, Iskandar Ali; Hairani, Hairani; Singagerda, Faurani Santi (International Journal of Energy Economics and Policy, 2019)
The increasing as non-food uses of vegetable oils especially as biodiesel and the basis of the oleo-chemical industry, making the formation of vegetable oil prices in world trade has been linked to world prices of crude oil in addition to linkages with the world price of vegetable oils competitor. The objectives of study were to analyze the linkage of the world price of crude and vegetable oil simultaneously, and examine the impact of the changes of the external factors and trade policy by the vegetable oil's exporting countries and importing countries on the world trade of vegetable oils, and particularly the production, domestic supply, domestic consumption and exports volumes of Indonesian palm oil. The study employed an econometric model and parameters were estimated using Two Stage Least Squares methods for the period 1990-2017. The study found that real price projections in the world market of 2012-2025 periods show the price fluctuations of crude oil and vegetable oil tend to have same patterns with slightly trend to increases. Although positively correlated, the percentage increase of vegetable oils price as the effect of the increasing of crude oil price is less than the percentage change of crude oil prices, except for soybean oil prices that vista vies with the percentage change of crude oil prices. The effect on percentage change of price of soybean oils is the highest and then followed by palm oil. Beside the chemical characteristics, the condition related to the limited volumes of vegetable oils world's productions and the food sector needs as a main constraints in the use of vegetable oils as crude oil substitutes. As annual crop commodities and the substitutes of seed oils, however, palm oil price has more responsive to export fluctuation then it. Keywords: price formation, world trade, vegetable oil, petroleum JEL Classifications: D43, F15, Q41, Q42 DOI: https://doi.org/10.32479/ijeep.7916